Psychosocial and socioeconomic impacts of atopic dermatitis: a comprehensive review - Ramli, Rizal Za'im; Ab. Hadi, Hazrina; Sarker, Zaidul Islam; Ahmad Alwi, Akmal Azim (IIUM Press, 2023)
Atopic dermatitis or eczema is a chronic inflammatory skin disease caused by several factors, including environmental allergens, family history of atopy, barrier dysfunction, and immune dysregulation. Eczema has been widely recognized worldwide for its adverse clinical and psychological effects. Besides affecting the physical appearances of the patients, the bad perceptions of the surrounding people, including friends, families, and strangers, toward the patients can worsen their mental health status and their quality of life. The burden of eczema has long been recognized as a socioeconomic and psychosocial burden worldwide, thus initiating some approaches towards improving awareness and better treatment that can lead to significant improvement in the quality of life of eczema patients worldwide. Two of the Global Burden of Disease (GBD) studies, International Study of Asthma and Allergies in Childhood (ISAAC) and other eczema skin studies are included in this review to study the global burden of this skin disease using the Disability-Adjusted Life Years (DALY) to assess the overall burden of the disease and estimating the prevalence of eczema worldwide. Regardless of eczema's direct or indirect cost, those effects have significantly changed the patients’ lives negatively; thus, it is an issue that needs to be addressed globally.